2014
DOI: 10.1016/j.epsr.2013.11.025
|View full text |Cite
|
Sign up to set email alerts
|

Measurements of harmonic emission versus active power from wind turbines

Abstract: a b s t r a c tThis paper presents harmonic measurements from three individual wind turbines (2 and 2.5 MW size). Both harmonics and interharmonics have been evaluated, especially with reference to variations in the active-power production. The overall spectra reveal that emission components may occur at any frequency and not only at odd harmonics. Interharmonics and even harmonics emitted from wind turbines are relatively high. Individual frequency components depend on the power production in different ways: … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(23 citation statements)
references
References 11 publications
0
22
0
1
Order By: Relevance
“…When the operating point varies, different PDFs are observed in [15]. Furthermore, in [6], the individual harmonics or inter-harmonics can be either dependent on or independent of the active power production. These various cases of harmonic generation imply that the stochastic characteristics of harmonic generation are different from case to case.…”
Section: The Relationship Between the Wind Turbine Operating Point Anmentioning
confidence: 99%
See 1 more Smart Citation
“…When the operating point varies, different PDFs are observed in [15]. Furthermore, in [6], the individual harmonics or inter-harmonics can be either dependent on or independent of the active power production. These various cases of harmonic generation imply that the stochastic characteristics of harmonic generation are different from case to case.…”
Section: The Relationship Between the Wind Turbine Operating Point Anmentioning
confidence: 99%
“…In particular, increasing attention has been drawn to power quality concerns: harmonics and the output harmonic impedance of wind turbines (WTs) and the aggregating WPP are stochastic due to the inherent intermittency of the wind and wide control bandwidth of the power electronics interfaces [6,7]. These wideband stochastic harmonic emissions from modern converter-based WTs may adversely interact with the grid via vast underground or submarine cable systems, leading to many series and parallel resonance points that significantly change with the harmonic filters, feeder configuration and reactive power compensation devices associated with the number of WTs in operation [1,[7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…Al incrementar la producción de potencia de un aerogenerador, el total de interarmonicos también aumenta. Los armónicos no dependen de la potencia activa de producción, mientras que los interarmonicos tienen una relación de dependencia con la potencia activa de producción (Yang et al, 2014), (Yeh & Huang, 2014).…”
Section: Transitoriosunclassified
“…This assumption is demonstrated to be valid when the interharmonic source is an EAF which mainly produces modulation of the fundamental voltage in the frequency range from 0 to 20 Hz, that is to say modulations produced by interharmonics in the frequency range from 20 to 80 Hz. Recent studies have demonstrated that modern distributed energy resources, in particular wind turbines, are able to produce interharmonics in a wide range of frequency from DC to some kilohertz [15]. Moreover, in [16][17][18], it was demonstrated that interharmonic components produced by adjustable speed drives can cover all the frequency range from DC.…”
Section: Introductionmentioning
confidence: 99%